Responses and influences: a model of online information use for learning - Hilary Hughes (Information Research: An International Electronic Journal)
Introduction. This paper explores the complexity of online information use for learning in the culturally diverse ICT-intensive higher education context. It presents a Model of responses and influences in online information use for learning that aims to increase awareness of the complexity of online information use and support information literacy development. Background. Despite increasing integration of information literacy into university curricula there are evident limitations in students' use of information associated with an information literacy imbalance between well developed information technology skills and uncritical approaches, compounded by differences in cultural and linguistic experience. Influences. This model draw insight from models of information behaviour and information seeking (Wilson, Foster, Kuhlthau), information literacy (Bruce), cross-cultural adaptation (Anderson), reflective online use (Hughes, Bruce and Edwards). The model. Incorporates behavioural, cognitive and affective responses with cultural and linguistic influences in an action research framework that represents online information use as holistic, dynamic and continuous, envisaged as the experience of engaging with online information for learning . Conclusion. The model represents the synergy between information use and learning. It supports the development of inclusive reflective approaches to information literacy that address identified learning challenges related to information literacy imbalance and cultural and linguistic diversity.